Unilateral sanctions in international law - Subedi, Surya P., 1958- (Oxford, UK ; New York, NY : Hart Publishing, an imprint of Bloomsbury Publishing, 2021)
"This is the first book that explores whether there are any rules in international law applicable to unilateral sanctions and if so, what they are. The book examines both the lawfulness of unilateral sanctions and the limitations within which they should operate. In doing so, it includes an analysis of State practice, the provisions of various international legal instruments dealing with such sanctions and their impact on other areas of international law such as freedom of navigation, aviation and transit, and the principles of international trade, investment, regional economic integration, and the protection of human rights and the environment. This study finds that unilateral sanctions by a state or a group of states against another state as opposed to 'smart' or targeted sanctions of limited scope would be unlawful, unless they meet the procedural and substantive requirements stipulated in international law. Importantly, the book identifies and consolidates these requirements scattered in different areas of international law, including the additional rules of customary international law that have emerged out of the recent practice of States and that increase the limitations on the use of unilateral sanctions"--
Introduction / Surya P Subedi -- The status of unilateral sanctions in international law / Surya P Subedi -- Shades of grey : autonomous sanctions in the international legal order / Nigel D White -- Unilateral sanctions : creating chaos at bargain rates / Joy Gordon -- The implications of unilateral sanctions for the freedom of aviation / Nick Grief -- The impact of unilateral sanctions on regional integration treaties with special reference to the gulf cooperation council / Ali Abusedra -- The effect of unilateral sanctions on foreign investors and the foreign investment regime / Nicolette Butler -- The World Trade Organisation and unilateral sanctions : prohibited or possible? / James Watson -- Unilateral sanctions, universal postal union and state responsibility / Trisha Rajput -- Unilateral coercive measures : towards international humanitarian law and international human rights / Louisa Ashley -- Maritime lawfare : the impact of unilateral sanctions on law and practice on navigation and seaborne trade / Abhinayan Basu Bal -- Can unilateral sanctions and international environmental obligations of states coexist? / Amrisha Pandey -- Use of cyber means to enforce unilateral coercive measures in international law / Ali Abusedra, Abu Bakar Munir and Md Toriqul Islam -- Conclusions : the current law on unilateral sanctions, remedies against unlawful use of such sanctions and recommendations / Surya P Subedi.
Includes bibliographical references and index.
Previously issued in print: Hart Publishing, 2021.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Sanctions (International law); Law; Public International Law (Law); International Economic and Trade Law (Law); International Investment Law (Law); International economic & trade law; Electronic books